IMPLEMENTASI PROGRAM PELATIHAN DAN PENGEMBANGAN KARYAWAN DI PT. TECHNINDO MANDIRI PERKASA - Yuli Indah Fajar Dini,; Eugene Kurniawan, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
This internship project aims to analyze and implement employee training and development programs at PT. Technindo Mandiri Perkasa, a company operating in the fields of Mechanical Electrical, HVAC, civil construction, and architecture. The technical complexity of the projects and strict safety requirements necessitate highly competent and adaptive human resources. Through interviews and field observations, gaps were identified in employee competencies, particularly in operating technical tools, maintaining HVAC systems, and understanding safety procedures. Based on these findings, a structured training module was developed, covering learning objectives, core materials, delivery methods, and performance indicators. The implementation of the training involved socialization sessions, material presentations, demonstrations, and hands-on practice. The results indicate significant improvements in employees’ technical skills, safety awareness, and operational efficiency. The designed training module is considered relevant, practical, and suitable for continuous implementation as part of the company’s human resource development framework. Overall, this project contributes substantially to enhancing employee competencies and strengthening PT. Technindo Mandiri Perkasa’s operational capacity in responding to the increasing demands of the construction and mechanical-electrical industry.